Let's perform the operations step-by-step:
-
Expand the expression \(-(2x + 6)(3x + 4)\): \[ -(2x + 6)(3x + 4) = -(2x \cdot 3x + 2x \cdot 4 + 6 \cdot 3x + 6 \cdot 4) \] Expanding: \[ = -(6x^2 + 8x + 18x + 24) = -(6x^2 + 26x + 24) = -6x^2 - 26x - 24 \]
-
Add \(5x^2 - 7x\) to \(-6x^2 - 26x - 24\): \[ -6x^2 - 26x - 24 + 5x^2 - 7x \] Combine like terms: \[ (-6x^2 + 5x^2) + (-26x - 7x) - 24 = -x^2 - 33x - 24 \]
So, the simplified expression is: \[ -x^2 - 33x - 24 \]
Now, checking the provided options:
- Option A: \(11x^2 + 19x + 24\)
- Option B: \(-x^2 + 3x + 24\)
- Option C: \(-x^2 - 33x - 24\)
- Option D: \(-x^2 - 19x - 24\)
The correct answer is C: \(-x^2 - 33x - 24\).